Single Site Experience of the use of Monoclonal Antibodies for the Treatment of COVID-19 in High-risk Pediatric and Young Adult Patients. Issue 12 (11th October 2022) - Bahakel, Hannah; Murphy, Catherine; Frenck, Robert W.; Grimley, Michael S.; Marsh, Rebecca A.; Paulsen, Grant C.; Haslam, David B.; Phillips, Christine L.; Courter, Joshua; Spearman, Paul; Schulert, Grant; Danziger-Isakov, Lara
Abstract : Background: Effective therapeutic agents for the treatment of COVID-19 have been investigated since the onset of the pandemic. Monoclonal antibodies targeting the spike protein of SARS-CoV-2 have been developed for the treatment of mild or moderate COVID disease in high-risk populations. Despite widespread use in the adult population, data are limited on the safety and efficacy of monoclonal antibody infusions in the adolescent and young adult population. Methods: Patients who received bamlanivimab, bamlanivimab-etesevimab, casirivimab-imdevimab, or sotrovimab for treatment of mild-to-moderate COVID-19 disease at Cincinnati Children's Hospital Medical Center from 5/1/2020 to 3/1/2022 were identified retrospectively. Patient data including demographics, adverse events, and outcomes were extracted from patients' charts and summarized by standard descriptive summaries. Results: Ninety-four patients received monoclonal antibody therapy, of which 14 (14.9%) received either bamlanivimab or bamlanivimab-etesevimab, 54 (57.4%) received casirivimab-imdevimab, and 26 (27.6%) received sotrovimab. Ten patients (10.6%) experienced one or more infusion-related adverse event. Of the patients who experienced adverse events, all resolved with cessation of infusion. No life-threatening events or deaths occurred. Within 90 days of receiving a monoclonal antibody, 12 patients (12.7%) required additional medical care for ongoing COVID symptoms. Five of these were either hospitalized or received escalation of care while already in the hospital. All subsequently fully recovered. Neither infusion-related adverse events nor progression to hospitalization for ongoing COVID-19 symptoms following monoclonal antibody administration were associated with any particular underlying condition. Conclusions: Overall, monoclonal antibodies are reasonably well-tolerated COVID-19 therapies in high-risk adolescent and young adult populations.